CONTRASTIVE STUDY OF POLITENESS STRATEGIES IN ENGLISH AND UZBEK COMMUNICATION: IMPLICATIONS FOR CROSS-CULTURAL INTERACTION - Kudratova Zilola Adkhamjonovna (Modern American Journals, 2025)
This article explores the development of the theory and practice of conceptualization in Uzbekistan, analyzing its formation, evolution, and modern application in linguistics and related fields. The study emphasizes the theoretical foundations of conceptualization, its methodological approaches, and practical significance in cognitive linguistics. Special attention is given to the influence of Uzbek cultural and linguistic traditions on the development of conceptualization, as well as to comparative perspectives with international experiences. The research findings highlight the importance of conceptualization theory in enhancing linguistic research, improving methods of language teaching, and strengthening intercultural communication. The work contributes to the understanding of how national traditions and global scientific approaches interact in the formation of conceptualization practices in Uzbekistan.
Keywords: Conceptualization, cognitive linguistics, theory and practice, Uzbekistan, linguistic tradition, methodology, intercultural communication, cognitive approach